Students’ Self-perception on their Mathematics Anxiety - Paudel, Krishna Chandra; Ghimire, Shree Prasad (Academic Journal of Mathematics Education, 2024)
Mathematics anxiety greatly affects students’ academic success and psychological well-being. This study explores math anxiety among 150 high school students in Kathmandu by investigating its prevalence, its sources, and potential methods for improving it. The research examined students’ perceptions of their mathematical anxiety across various educational stages using a combination of quantitative surveys and semi-structured interviews. The findings indicated that 60% of students recognized experiencing mathematical anxiety related to a figure that increased to 86.67% after an educational intervention. The study discovered that the majority of students experience math anxiety during high school (48%) time, and they hold different perspectives on ways to reduce it. It was found that 68% of students expressed the ability to manage anxiety on their own and understand that anxiety is temporary. The study emphasizes the significance of providing personalized psychological guidance and individualized intervention strategies to support students’ mathematical learning experiences and overall well-being.